KONSEP JUAL BELI, RIBA DAN GADAI PERSPEKTIF AL-QUR’AN DAN AL- HADITS - MUHAMMAD HARIS HIDAYATULLOH (ITB AAS INDONESIA Surakarta, 2023)
This study aims to find out what buying and selling, usury and pawning are like in the view or perspective of the Koran and al hadith. In this study using a qualitative literature study methodology, the data used, of course, used primary data and secondary data and used some literature related to the title of this study. The result of this research is to find out how the concept of buying and selling is regulated in the Qur'an and hadith as well as the concept of usury and mortgage. In buying and selling according to the Qur'an and hadith here there are more regulations and prohibitions related to activities such as fraud and the need for honesty in accordance with the teachings of the Prophet when carrying out trading activities, while the issue of usury is of course this is strictly prohibited in the Koran and hadith even in other religions also prohibits the concept of usury itself, related to the problem of pawning in this case, it has been explained that many things are permissible in this pawning practice and even the Prophet Muhammad saw practiced it, thus this is permissible on condition that it does not violate the rules of the Koran and hadith.